LESSONS WE CAN LEARN ABOUT HUMAN RIGHTS AFTER THE COVID-19 VIRUS PANDEMIC IN THE REPUBLIC OF SERBIA - Sanela Veljković (Pravo, 2023)
The spread and danger of the Covid-19 virus in 2020 demonstrated how unprepared states were for such threats. Each state took measures it believed to be adequate at the time to protect its population. In the Republic of Serbia, numerous measures were implemented after a state of emergency was declared in March, to prevent the spread of the virus. Many of these measures led to derogations of various human rights. However, even in extreme situations like a state of emergency, derogating human rights should meet the requirements of necessity, and proportionality. This paper examines the state of certain human rights, namely the right to information and freedom of peaceful assembly during the state of emergency in the Republic of Serbia. The analysis aims to determine whether there was a derogation of these rights or rather their gross violation. In this way, the paper seeks to provide specific lessons about human rights that every citizen can draw after the Covid-19 virus pandemic in the Republic of Serbia.